Comparison of Lecturing and Multimedia-Based Learning on the Knowledge and Remembrance of Breast Cancer Topics in Midwifery Students of Shiraz University of Medical Sciences in 2016 (Bangladesh Journal of Medical Science, 2020)
Background and Purpose: One of the most important principles of training is the appropriate teaching method. The method used plays a key role in the process of teaching and learning and affects the students’ learning while knowledge of these methods and choosing the best of them lead to improvement in education. The aim of this study was to compare the effect of two lecturebased and multimedia-based training methods on learning, knowledge and remembrance of breast cancer topics in students of Shiraz University of Medical Sciences in 2016.Methods: In a quasi-experimental study, 42 midwifery students were assigned to two groups for training (25 students in multimedia-based method and 18 in lecture-based method). The students’ knowledge was measured using 20 multiple-choice questions designed by the researcher in three stages: pre-test, post-test and test-retest (2 months after the intervention). Then, the data were analyzed using SPSS, 19, at a significance level of 95%.Findings: There was no significant difference between the students’ mean age and their mean score in the course of women’s diseases in the two groups. No difference was observed in the mean scores in the two groups (p>0.05) before the intervention, but after the intervention the level of students’ knowledge in both groups increased (p=0.000). In the post-test stage, there was a significant difference between the scores in the multimedia-based and lecture-based groups (p=0.000).Results: The results indicated the effectiveness of multimedia knowledge and breast training method so that this method showed a more lasting knowledge after two months of training.Bangladesh Journal of Medical Science Vol.19(4) 2020 p.710-716